2008
DOI: 10.1016/j.juro.2008.01.096
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Female Stress Urinary Incontinence

Abstract: Purpose-Urinary incontinence affects 40% of women in the United States and stress urinary incontinence accounts for a large portion of affected patients. As defined by the International Continence Society, stress urinary incontinence is the involuntary leakage of urine upon effort, exertion, sneezing or coughing. Since the ultimate success of long-term management for any condition is based on an understanding of its pathophysiology, and because the pathophysiology of stress urinary incontinence is incompletely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
84
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 59 publications
1
84
0
Order By: Relevance
“…VD has been extensively used as an experimental model to serve as a simulation of the tissue damage incurred as a result of vaginal childbirth (6,10,17,22,26). Histological results in our study demonstrated muscle injuries with increased fiber disruption, atrophy and waviness in the urethra after either PNC or VD.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…VD has been extensively used as an experimental model to serve as a simulation of the tissue damage incurred as a result of vaginal childbirth (6,10,17,22,26). Histological results in our study demonstrated muscle injuries with increased fiber disruption, atrophy and waviness in the urethra after either PNC or VD.…”
Section: Discussionmentioning
confidence: 52%
“…Vaginal distension (VD) and pudendal nerve crush (PNC) in rats are two relevant and well-established animal models of SUI of simulated childbirth (10,17,22,26). Numerous studies have demonstrated that these injuries in rats can represent the clinical injuries of vaginal childbirth in women since both lead to decreased urethral closure ability, decreased leak point pressure (LPP), and symptoms of SUI (6,10,22,26,31).…”
mentioning
confidence: 99%
“…In the United States, more than 165,000 surgical procedures have been performed for stress UI [2]. In Australia alone, the total annual cost of UI was estimated to be USD 710.44 million in 1998 and is projected to be USD 1.27 billion by the year 2018 [3].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of life of women with UI is significantly worse than that of women without it. It has been reported that UI affects 40% of women in the United States [2]. China is a developing country and is becoming an aging society.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of neurologic diseases can induce dysfunction of bladder outlet thereby altering the coordination between bladder and external urethral sphincter (EUS), which impedes urine outflow and compromise voiding efficiency (Cheng and de Groat, 2004). They can also damage the motor innervation of EUS resulting in loss of guarding function and urinary incontinence during storage phase (Hijaz et al, 2008). All of these disorders may lead to urological complications such as urinary retention, bladder hypertrophy, urinary infection, and deterioration of renal function.…”
mentioning
confidence: 99%